Pemanfaatan Perpustakaan Sekolah sebagai Sumber Belajar Pendidikan Agama Islam di SMK Swasta Al Bukhary Rantauprapat - Pratiwi Ritonga, Livsih Suci; Siagian, Taufiqqurrahman Nur; Budiman, Syahrul (MODELING: Jurnal Program Studi PGMI, 2024)
This study examines the utilization of the school library as a learning resource for Islamic Religious Education (PAI) at SMK Swasta Al Bukhary Rantauprapat. This research employs a descriptive qualitative approach. Data collection techniques include observation, interviews, and documentation. The validity of the data is ensured through triangulation, which involves comparing various sources of information obtained from observations, interviews, and documentation to enhance accuracy and reduce bias in data analysis. The data analysis techniques used in this study consist of data reduction, data presentation, and drawing conclusions.The results indicate that the school library serves as a learning resource center that provides book collections and supporting facilities, although the availability of Islamic literature remains limited. The utilization of the library by students for PAI learning is still suboptimal, with visits mostly occurring only when assigned by teachers. Supporting factors for library utilization include the availability of book collections, adequate facilities, and teacher support. Meanwhile, inhibiting factors include low student reading interest, limited specific Islamic book collections, a lack of literacy activities, and time constraints. Nevertheless, for students who utilize the library, it contributes to improving their understanding of PAI material, fostering reading interest, and strengthening critical thinking skills in comprehending Islamic teachings. Strategic efforts from the school are needed to optimize library utilization, including expanding the collection of Islamic books and organizing religion-based literacy activities.